2012
DOI: 10.1002/ajh.23261
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of reduced‐intensity allogeneic hematopoietic stem cell transplantation for refractory or relapsed follicular lymphoma

Abstract: Although allogeneic hematopoietic stem cell transplantation (HSCT) is considered the only curative treatment for refractory or relapsed follicular lymphoma (FL), transplant-related mortality (TRM) greatly interferes with the success. A variety of reduced-intensity conditionings (RICs) have been used to reduce TRM, but an optimal conditioning for FL has not been fully established. We retrospectively evaluated the outcome of allogeneic HSCT for FL with RIC consisting of fludarabine and melphalan. Nineteen adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Although the availability of rituximab has improved both the outcome and survival of FL [22,23], patients with relapsed or refractory FL are advised to undergo allo-HSCT before they receive excessive chemotherapies and their physical condition is exacerbated by the adverse effects. The previous reports of allo-SCT for relapsed and refractory FL are summarized in Table3 [8,[24][25][26][27][28][29][30][31][32]. PFS and OS rates among the patients who received allo-SCT with RIC varied between approximately 40% and 80%, which was almost equivalent to those of our result.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although the availability of rituximab has improved both the outcome and survival of FL [22,23], patients with relapsed or refractory FL are advised to undergo allo-HSCT before they receive excessive chemotherapies and their physical condition is exacerbated by the adverse effects. The previous reports of allo-SCT for relapsed and refractory FL are summarized in Table3 [8,[24][25][26][27][28][29][30][31][32]. PFS and OS rates among the patients who received allo-SCT with RIC varied between approximately 40% and 80%, which was almost equivalent to those of our result.…”
Section: Discussionsupporting
confidence: 79%
“…A comparative retrospective study revealed a significantly lower relapse rate in patients with relapsed FL who underwent allo-SCT compared with those who underwent autologous SCT (auto-SCT) or salvage chemotherapy [5,6]. Therefore, allo-SCT has become the treatment of choice for patients with relapsed or refractory FL [7,8]. However, the potential survival benefits of allo-SCT compared with that of auto-SCT is often offset by the high treatment-related mortality (TRM) rate, due to direct toxicity and high incidence of severe graft-versus-host disease (GVHD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in 2 retrospective studies of allo-SCT for relapsed or refractory FL from Japan, using FM (Flu and Mel)-based or FB (Flu and Bu)-based RIC in a majority of cases, 49,50 the percentages of patients who had chemoresistant disease at allo-SCT were notably higher (63%-68%) than from other series from North America or Europe (Table 2). Nevertheless, the 5-year PFS and OS in those studies were 70%-84% and 77%-84%, respectively, with low NRM (16% for each study).…”
Section: Reduced-intensity Conditioning Allo-sctmentioning
confidence: 82%
“…There were 46 patients identified as being eligible for the study, and 19 of them have been reported previously. 15…”
Section: Patients and Methods Patientsmentioning
confidence: 99%